A 1‐year follow‐up study of the longitudinal interplay between emotion dysregulation and childhood trauma in the treatment of anorexia nervosa. Issue 1 (4th December 2021) - Cassioli, Emanuele; Rossi, Eleonora; D'Anna, Giulio; Martelli, Michela; Hazzard, Vivienne M.; Crosby, Ross D.; Wonderlich, Stephen A.; Ricca, Valdo; Castellini, Giovanni
Abstract: Objective: The study aimed to investigate the complex relationship between eating disorder (ED) specific psychopathology, emotion dysregulation, and their longitudinal variations in patients with anorexia nervosa (AN) treated with a multidisciplinary approach including enhanced cognitive‐behavior therapy (CBT‐E), and to provide an integrated model which includes childhood trauma as a predictor of worse treatment outcomes. Method: In total, 120 female patients with AN were evaluated at admission (T0), and 105 were re‐evaluated after 1 year (T1) of treatment. At T0, patients underwent a clinical assessment and filled the Symptom Checklist 90‐Revised (SCL90‐R), the Eating Disorders Examination Questionnaire (EDE‐Q), the Difficulties in Emotion Regulation Scale (DERS), and the Childhood Trauma Questionnaire (CTQ). SCL‐90‐R, EDE‐Q, and DERS were readministered at T1. Variations between T0 and T1 were evaluated, and the proposed model was investigated using bivariate latent change score analysis in a structural equation modeling (SEM) framework. Results: An overall significant clinical amelioration was observed after treatment. A unidirectional effect of DERS scores on EDE‐Q variations was outlined by SEM: patients with higher baseline DERS scores achieved less EDE‐Q improvements, and EDE‐Q latent change score was significantly predicted by longitudinal variations of DERS—but not vice versa. Higher CTQ scores predicted reduced treatment efficacy for ED‐specific psychopathology through the mediating effect of higher baseline DERS scores. Discussion: The present study sheds light on the mechanism by which early trauma compromises treatment outcome in patients with AN, underlining the crucial role of emotional dysregulation.